Frege on absolute and relative truth : an introduction to the practice of interpreting philosophical texts - Pardey, Ulrich, 1946- (History of analytic philosophy., 2012)
Frege's essay 'Der Gedanke' ('Thoughts') is one of the best-known and most-quoted texts in the area of analytic philosophy. However, his arguments against the correspondence theory of truth, which are located in the third paragraph of 'Der Gedanke', are generally rejected on the grounds that they allegedly contain some easily identifiable logical errors. This is the view of leading Frege scholars such as Dummett, Kunne and Soames. Against this view the author proposes an entirely new interpretation of the text to show that Frege's argumentation is consistent. The central point of the author's interpretation is Frege's distinction between absolute and relative truth. Due to the detailed interpretation of Frege's text and the comprehensive refutation of misinterpretations of it by Dummett and other scholars, the book is also well suited to be a sophisticated introduction to the practice of interpreting philosophical texts for advanced students of philosophy. For this reason it also contains two chapters reflecting on the route and manner of the proposed new interpretation.